COMMUNICATION RELATIONSHIP WITH NURSE PATIENT SATISFACTION THAT TREATED IN ROOM KANA GATOEL HOSPITAL - Darsini (NurseLine Journal, 2016)
Medical technical skills alone are not sufficient to provide satisfactory service patient, it takes good communication between health workers or nurses with patients. Effective communication includes verbal and nonverbal communication effectively. The aim of this study knowing nurse communication relationship with the level of satisfaction of patients treated in the room Kana Gatoel Hospital Mojokerto. This type of research is an analytic correlation with the study design was cross-sectional design. Independent vari- ables nurse communication. The populations are all patient populations Kana Gatoel Hospital Mojokerto as many as 54 patients. The sampling technique used is the type of probability sampling simple random sampling. This study was conducted on 13 July